Rethinking Trademark Dilution in Jordan: Addressing Ambiguities and Aligning with Global Standards - Shatha Majid Shannag; Subhajit Basu (Laws, 2025)
This paper critically analyses the application of the trademark dilution doctrine under Jordanian trademark law, exposing fundamental deficiencies arising from statutory ambiguity and inconsistent judicial interpretation. The indeterminate definition of a “well-known” trademark in the second section has led to an indiscriminate classification of foreign marks as inherently well-known, resulting in courts extending automatic dilution protection without a rigorous evidentiary assessment. This practice fosters an implicit presumption favouring foreign trademark holders, potentially disadvantaging domestic marks that may not receive commensurate protection, thereby undermining the principle of equitable trademark enforcement. This paper argues for a systematic recalibration of Jordan’s dilution framework. A comparative analysis of the well-established dilution doctrines in the United States and European Union identifies jurisprudential best practices that could enhance the doctrinal coherence and judicial application of dilution protection in Jordan. Furthermore, drawing on the WIPO Joint Recommendation as a normative foundation, the paper proposes legal reforms to rectify inconsistencies, ensuring a more balanced and principled approach to trademark dilution. We argue that aligning Jordan’s legal framework with international standards strengthens the discourse on harmonising intellectual property law and ensuring equitable trademark protection in emerging markets.